Aplikasi Model Hidrologi Konseptual Untuk Pengalihragaman Hujan Debit Menggunakan Pendekatan GR4J (Studi Kasus : Sub Das Indragiri Bagian Hulu) - Safari Tri Septanto; Imam Suprayogi; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
On this study to review the rainfall-runoff modeling of GR4J (Ge'nie Rural a`4parame`tres Journalier) on Watershed (DAS) Indragiri Bagian Hulu. In this study using two methods:by modeling GR4J and length of the data elaboration method for calibration and verification. This GR4J models using input data including daily data of rainfall at the Lubuk Ramo stationand daily data of evapotranspiration potential is the result of a program CropWat within input data is climatological data at Sentajo stations, modeling results is tested using daily data of discharge observations on the Pulau Berhala station. This modeling to optimize four free parameters such as Maximum Capacity Production Store (X1) is 1200,00 mm, Coefficient Changes in Ground water (X2) is 3,00 mm, Maximum Capacity Routing Store (X3) is 20,00 mm, and Peak Time Ordinate unit hydrograph (X4) 24,75 days. In the second method, performed of calibration in certainly year and verification in thereafther. As a determinant of the model’s success is use dequation NashSutcliffe Coefficient (R2) and the correlation coefficien tmethod (R) to calculate the deviation occurs.Keywords : GR4J, Calibration, Verification.